Who's cooking tonight? A time-use study of coupled adults in Toronto, Canada. (November 2022) - Liu, Bochu; Widener, Michael J; Smith, Lindsey G; Farber, Steven; Gesink, Dionne; Minaker, Leia M; Patterson, Zachary; Larsen, Kristian; Gilliland, Jason
Understanding how coupled adults arrange food-related labor in relation to their daily time allocation is of great importance because different arrangements may have implications for diet-related health and gender equity. Studies from the time-use perspective argue that daily activities such as work, caregiving, and non-food-related housework can potentially compete for time with foodwork. However, studies in this regard are mostly centered on individual-level analyses. They fail to consider cohabiting partners' time spent on foodwork and non-food-related activities, a factor that could be helpful in explaining how coupled partners decide to allocate time to food activities. Using 108 daily time-use logs from seventeen opposite-gender couples living in Toronto, Canada, this paper examines how male and female partners' time spent on non-food-related activities impact the total amount of time spent on foodwork by coupled adults and the difference in time spent on foodwork between coupled women and men. Results show that both male and female partners took a higher portion of foodwork when their partner worked longer. When men worked for additional time, the couple-level duration of foodwork decreased. Without a significant impact on the gender difference in foodwork duration, women's increased caregiving duration was associated with a reduction of total time spent on foodwork by couples. An increase in caregiving and non-food-related chores by men was associated with an increased difference in duration of foodwork between women and men, which helped secure a constant total amount of foodwork at the couple level. These behavioral variations between men and women demonstrate the gender differences in one's responsiveness to the change of partners' non-food-related tasks. The associations found among non-food-related activities and foodwork are suggestive of a need to account for partners' time allocation when studying the time-use dynamics of foodwork and other daily activities.